Multi-dimensional architecture of Ag/alpha-Ag2WO4 crystals: insights into microstructural, morphological, and photoluminescence properties - Cruz, Lilian; Teixeira, Mayara M.; Teodoro, Vinicius; Jacomaci, Natalia [UNESP]; Laier, Leticia O. [UNESP]; Assis, Marcelo; Macedo, Nadia G.; Tello, Ana C. M.; Silva, Luis F.; Marques, Gilmar E.; Zaghete, Maria A. [UNESP]; Teodoro, Marcio D.; et al. (Royal Soc Chemistry, 2020)
In this study, we report the potential of ethylenediamine (En) in the modification of the morphological, structural, optical and catalytic properties of alpha-Ag2WO4 crystals decorated with Ag nanoparticles (Ag NPs). Experimental techniques were used to characterize the as-synthesized samples such as X-ray diffraction, Raman, electron microscopy, X-ray photoelectron spectroscopy, X-ray absorption spectroscopy, and photoluminescence spectroscopy. The results confirmed the efficiency of En in the decoration with the formation of Ag/alpha-Ag2WO4 crystals and also the modification of alpha-Ag2WO4 morphology that indicated its influence on the crystal growth mechanism via self-assembly and Ostwald ripening. En affects the degree of order/disorder of the crystalline structures in long and short-ranges. In addition, photoluminescence measurements revealed a blue shift of the optical emission caused by a reduction of oxygen vacancies and an increase in structural disorder due to the En concentration used in the synthesis processes. Regarding the photocatalysis experiments, the reduction in oxygen vacancies also caused a decrease in the photoactivity of alpha-Ag2WO4 against the rhodamine B dye, thus confirming the relevance of oxygen vacancies for the development of alpha-Ag2WO4 photocatalysts.